Endophytic Fungi of Dragon Fruits: Diversity and Its Potential as Biocontrol Agents of Stem Canker Disease Neoscytalidium dimidiatum - Nugraha, Andhika Vidian; Giyanto, Giyanto; Tondok, Efi Toding (AGRIVITA Journal of Agricultural Science, 2026)
Endophytic fungi have the potential for antagonistic activity against plant pathogens and can be utilized to prevent the decline in dragon fruit production caused by stem canker disease. This study aims to assess the diversity of endophytic fungi in highland and lowland areas and to evaluate their potential against dragon fruit stem canker disease. Research has been conducted using several methods, i.e., isolation of endophytic fungi from dragon fruit, biosafety assay, potential assay, and semi-in vivo assay. Banyuwangi and Bukittinggi have moderate diversity, relatively even species distributions, and low-to-moderate dominance of particular isolates. Isolates Trichoderma sp. C6 and Trichoderma sp. C13 are able to inhibit the development of N. dimidiatum on wounded cladodes. Molecular identification showed that Trichoderma sp. C13 has a close phylogenetic relationship with T. hamatum T311. Endophytic fungi from dragon fruit plants may serve as potential biocontrol agents against N. dimidiatum. However, the mechanism by which these endophytic fungi induce resistance in dragon fruit plants against N. dimidiatum remains unclear and warrants further investigation.